Gender Inequalities in Academic Achievement among Internally Displaced children in Colombia - Silva-Arias, Adriana Carolina; Sarmiento-Espinel, Jaime Andrés; Gónzalez-Cogollos, Laura Victoria (Revista Latinoamericana de Ciencias Sociales, Niñez y Juventud, 2020)
Abstract Using 2015 data of the Colombia Demographic and Health Survey, we investigated the incidence of belonging to a household with an Internally Displaced Person (IDP) on the likelihood of grade retention by sex. Particularly, a bivariate logistic regression was used to identify the correlation between families with IDP and children’s gender on the probability of repeating a school year. Boys’ were negatively affected when they live in an IDP household. Also, boys had a higher likelihood of repeating a grade. We need to know how to act upon the social determinants that create social gaps and disadvantages across IDP, but also, to align with Sustainable Development Goals to eliminate gender inequalities. Keywords: Academic Failure, Grade Repetition, Violence, armed conflicts, gender roles, civil war, Disadvantaged groups, Displaced Persons, War Victims.